POLITICS OF THE DEATH PENALTY IN CORRECTIONAL PERSPECTIVE - Afan Rifanizar (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The application of capital punishment is very much reaping the pros and cons, especially for countries that have a retention of understanding with abolitionist countries in viewing the sentence. In Indonesia, the death penalty has increased especially after the government's seriousness in combating drug crimes and terrorism. The research method used by researchers in this study is a normative legal research method by examining several scientific literatures such as scientific journals, books, government agency data reports combined with related news by trusted media. This study aims to provide an analysis of the rules of the death penalty in a human rights perspective by comparing it with the concept of correctional facilities, as well as providing more knowledge to the public and can be used as material that can be considered for policy makers in the application of criminal justice.